Odpowiedzi

2009-12-07T18:33:24+01:00
A) 3t-s=2
4t+s=5

7s=7
s=1

3t-s=2
3t-1=2 |+1

3t=3
t=1

b) 17p+13q=4
11p-q=12 |*13

17p+13q=4
143p-13q=156

160p=160
p=1

17p+13q=4
17+13q=4 |-17

13q=-13
q=-1
  • liz2
  • Początkujący
2009-12-07T18:38:36+01:00
3t-s=2
4t+s=5

3t+4t=2+5
7t=7 /: 7
t=1

3*1-s=2
3-2=s
s=1
________________________________________________

17p+13q=4
11p-q=12 /*13

17p+13q=4
143p-13q=156

160p=160 /:160
p=1

17*1+13q=4
17+13q=4
13q=4-17
13q=-13/:13
q=-1

2009-12-07T18:42:17+01:00
A) 3t-s=2
4t+s=5

7t=7
t=1

(3*1)-s=2
3-s=2
3-2=s
s=1

t=1
s=1